2012
DOI: 10.1016/j.rbmo.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Perception of control, coping and psychological stress of infertile women undergoing IVF

Abstract: The study aimed to examine: (i) the association between perception of infertility controllability and coping strategies; and (ii) the association between perception of infertility controllability and coping strategies to psychological distress, applying multivariate statistical techniques to control for the effects of demographic variables. This cross-sectional study included 137 women with fertility problems undergoing IVF in a public hospital. All participants completed questionnaires that measured fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 42 publications
10
79
0
Order By: Relevance
“…The findings of the literature reviews have revealed that positive coping strategies are related to the psychological well-being of women undergoing IVF treatment [43,44]. It has also been proposed that positive dyadic coping could reduce the stress for each partner and improve the functioning of the relationship of couples coping with stress [30,45].…”
Section: The Focuses Of the Complex Interventionmentioning
confidence: 99%
“…The findings of the literature reviews have revealed that positive coping strategies are related to the psychological well-being of women undergoing IVF treatment [43,44]. It has also been proposed that positive dyadic coping could reduce the stress for each partner and improve the functioning of the relationship of couples coping with stress [30,45].…”
Section: The Focuses Of the Complex Interventionmentioning
confidence: 99%
“…There have been reports of adverse effects on the psychological health of women who receive ART infertility treatment, including a high state of anxiety and a tendency to develop depression . However, a meta‐analysis of 14 prospective studies of infertile women concluded that neither anxiety nor depression affects the ART fertility rate .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, support could be offered to those who feel they cannot cope with the burden of treatment, but still are willing to become pregnant. These couples could benefi t from some additional support, for example an extra consultation with their physician or referral to a counsellor Gourounti et al, 2012). The problem in differentiating between these types of discontinuation has already been discussed (Van den Broeck et al, 2010).…”
Section: Discussionmentioning
confidence: 99%